Mental toughness and dietary behaviours in undergraduate university students. (1st November 2019) - Stamp, Elizabeth; Crust, Lee; Swann, Christian
Abstract: Dietary behaviour of university students is a growing concern and a potential contributor to weight gain during university studies. Individual differences may be one factor that influences how students respond and adapt when entering a new environment. Mental toughness (MT) is an individual difference which has previously been found to be significantly and positively related to health behaviours (e.g., physical activity, psychological wellbeing), thus it was hypothesised that MT would predict eating behaviours of university students. Undergraduate students (n = 167) completed an online questionnaire to assess MT and eating behaviours. Students were included from all three years of undergraduate study and from a range of courses at nine UK institutions. Pearson correlations were conducted between MT variables and eating behaviour variables. The MT component life control displayed the strongest relationship with healthy eating (r = 0.24, p < .001). Regression analysis found weak relationships between the components of MT that were related to eating behaviours. Thus, factors other than MT may play a greater role influencing eating behaviours of university students. It may be that MT is more important in adhering to programmes to change dietary behvaiours, rather than simply eating healthily.